The Effects Comparisons of Sauropus androgynous, Moringa oleiefera alone and in combination on iron deficiency in anemia rats (Bangladesh Journal of Medical Science, 2018)
Background: Leaves extract of Sauropus androgynous (Sa) or Moringaoleiefera(Mo) alone has been shown to increase hemoglobin level in iron deficiency anemia. The combination of the two extracts have been known to potentially have a synergistic effect on anemia. The objective of this study is to compare the anti-anemic effect of Sa, Mo alone and their combination on iron deficiency anemia in rats.Methods: Thirty female wistarstrain rats were randomly divided into 5 groups: normal, iron deficiency anemia, Sa, Mo and the combination of Sa and Mo. Beside the normal group, rats were fed Fe-deficient diet to induce iron-deficiency anemia. Level of hemoglobin, ferritin and plasma MDA were measured on day 8 (after induction of anemia) and day 29. Data were analyzed using One Way ANOVA followed by LSD post hoc test.Result: The rats fed with Fe-deficient diet for 7 days shown significantly had a lower plasma Hb and ferritin levels and higher plasma MDA levels compared to the normal group (p